Urban or moral decay? The case of twentieth century Detroit - Fahey, Carolyn (Journal of Architecture and Urbanism, 2017)
This paper provides an alternative narrative of Detroit from one of economic struggle and racial division. It instead discusses other forces at play, focusing on questionable moral standing and its relationship to built form, specifically the city. The paper explores whether a compelling claim on building’s moral use can be established, and in doing so seeks to establish a causal link between moral relationship and the built environment. Moral relationship is established through three main avenues. The first is a brief discussion of Detroit’s history, particularly its history from WWII onward, in order to establish the complex moral context into which this argument is situated. The second avenue provides a concise summary of Stanley Cavell’s moral framework and discusses the conundrum of having moral obligation in the absence of moral relationship. The final avenue is a look to the famous Renaissance Center as emblematic of the moral relationship at play. The resulting form of analysis relies on the premises that buildings can embody the knowledge and agreement required for (moral) relationship, and that buildings are artifacts of moral relationship. The paper concludes that buildings are therefore morally appraisable, which is to say they can be appraised for their moral appropriateness.First published online: 14 Jun 2017